Comparative anticancer effects of Annona muricata Linn (Annonaceae) leaves and fruits on DMBA-induced breast cancer in female rats - Kevine Kamga Silihe; William Defo Mbou; Judith Christiane Ngo Pambe; Larissa Vanelle Kenmogne; Laure Fotso Maptouom; Marius Trésor Kemegne Sipping; Stéphane Zingue; Dieudonné Njamen (BMC, 2023)
Abstract Background Numerous studies have reported the anti-cancer effects of different parts of Annona muricata Linn, however ; most of them focused on the in vitro evaluation of isolates. In vivo evidence on which part is best suited for breast cancer chemoprevention remains to be demonstrated. This is a comparative study of the effects of A. muricata fruit and leaves extracts on DMBA induced-breast cancer in rats. Methods Rats exposed to DMBA (50 mg/kg, s.c.), were treated with A. muricata fruit aqueous extract at 200 mg/kg BW (3 days/week or daily) and A. muricata Linn leaves ethanolic extract at 200 mg/kg daily. Positive control group received tamoxifen at 3.3 mg/kg, while the normal and diseased controls received vehicle. After 20 weeks of treatment, the tumor incidence, tumor burden, tumor volume, histopathology, protein and CA 15 − 3 levels as well as antioxidant status, pro-inflammatory cytokines were assessed. Results Thus, 100% of diseased rats presented cribriform ductal carcinoma of SBR grade III. A. muricata extracts (leaves and fruit) and tamoxifen significantly reduced death and tumor incidences, volume and weight of the tumors, total protein and CA15-3 levels compared to the DMBA group. They exhibited antioxidant activity, through an increase in the GSH level and SOD and catalase activities with reduced levels of MDA compared to DMBA group. TNF-α, IL-6 and INF-γ levels reduced with regards to A. muricata treatment. Conclusion These results confirm the anti-breast cancer effect of A. muricata, however, the aqueous fruit extract was more potent than the ethanolic leaves extract.